Improving BUMDes Management Capabilities Through Training on Organizational Management, Finance and Digital Marketing (BUMDes Margamulya Kec. Cileles Lebak Banten) - Manggabarani, Alfatih S.; Marlina, Marlina; Miftah, Munasiron (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
BUMdes in Cileles Sub-district, Lebak Regency are an organization that was only established in 2016. The establishment of BUMdes as a form of the village government's efforts to increase the village's original opinion and improve the living standards of Margamulya Village residents. through the first years of the establishment of BUMdes which is the most critical stage with the highest failure rate in the life cycle of the organization. This phenomenon is called the liability of newness, a high failure for new organizations because there is no formal structure in the process of generating added value and the existence of a standard and definite work procedure system. Through the BUMdes management training program emphasizing professionalism in financial and marketing management. The preparation of work plans as a work reference and supported by documented work procedures and division of tasks, authority and reporting becomes the BUMdes strength in ensuring the sustainability of the organization. aims to: (1) Help provide for the operational needs of BUMdes; (2) Train in finance, marketing and BUMDes/organization; (3) Create members who have commitment and loyalty high; (4) Train members to entrepreneur; (5) Partner Non Productive (Knowledge Increase, Skill Increase, Revenue Increase, Service Increase).